2013
DOI: 10.5194/acp-13-3063-2013
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone changes, radiative forcing and attribution to emissions in the Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP)

Abstract: Ozone (O3) from 17 atmospheric chemistry models taking part in the Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP) has been used to calculate tropospheric ozone radiative forcings (RFs). All models applied a common set of anthropogenic emissions, which are better constrained for the present-day than the past. Future anthropogenic emissions follow the four Representative Concentration Pathway (RCP) scenarios, which define a relatively narrow range of possible air pollution em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
434
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 406 publications
(465 citation statements)
references
References 92 publications
27
434
2
2
Order By: Relevance
“…In the UT, ozone is an important greenhouse gas with an estimated global-averaged radiative forcing of 0.40±0.20 W m −2 (Stevenson et al, 2013;IPCC, 2013), and it contributes greatly to the oxidation efficiency of the atmosphere. Ozone is the primary tropospheric source of hydroxyl (OH) and peroxy (RO x ) radicals, which affect the lifetime of other greenhouse gases such as methane CH 4 (Crutzen, 1974;Shindell et al, 2009;Cooper et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the UT, ozone is an important greenhouse gas with an estimated global-averaged radiative forcing of 0.40±0.20 W m −2 (Stevenson et al, 2013;IPCC, 2013), and it contributes greatly to the oxidation efficiency of the atmosphere. Ozone is the primary tropospheric source of hydroxyl (OH) and peroxy (RO x ) radicals, which affect the lifetime of other greenhouse gases such as methane CH 4 (Crutzen, 1974;Shindell et al, 2009;Cooper et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We calculate a value of f of 1.43 which is at the mid-upper end of the literature range (1.19-1.53) (Prather et al, 2001;Stevenson et al, 2013;Voulgarakis et al, 2013) and within 7 % of the observationally constrained best estimate of 1.34 (Holmes et al, 2013). 10…”
Section: Methane Feedback and Resulting Ozone Forcingmentioning
confidence: 99%
“…Other modelling studies focused on the radiative effects of mainly tropospheric ozone changes under future emission scenarios in a non processed-based fashion (e.g. Gauss et al, 2003;Stevenson et al, 2013). One study has recently identified the indirect tropospheric and stratospheric ozone RF between 2000 and 2100 due to individual perturbations (Banerjee et al, 2017) Here we aim to narrow this gap by assessing how key factors drive net ozone radiative forcing, and provide a gauge of the uncertainty arising from non-linearities and long-term feedbacks.…”
Section: Precursor 30mentioning
confidence: 99%
See 2 more Smart Citations